Trajectory-based operation monitoring of transition procedure in multimode process. (December 2020) - Wang, Zhaojing; Zheng, Ying; Wong, David Shan-Hill
Abstract: Many continuous industrial processes operate in different steady states with different grades or products. The switching between two steady states is called transition. Transition consists of a series of operation changes that should be carried out in proper order, within certain magnitudes and time region. Since faulty operation may lead to increase in inferior products or even hazard events, monitoring of the transition is desired. In this work, a transition identification and monitoring scheme is proposed based on slow feature analysis. Two monitoring statistics which represent the location of the trajectory and the speed of transition are proposed. Besides, operating faults are generated based on the guidewords of hazard and operability analysis (HAZOP). Using a numerical case and the mode 4-to-2 transition of the Tennessee-Eastman process in which catastrophic failures exist, the effectiveness of the proposed method is validated. In addition to missed detection rate and false alarm rate, two performance indexes known as detection time (DT) and rescue time (RT) are introduced. The advantages of proposed method are benchmarked against the stage-based sub principle component analysis(sub-PCA) and the global preserving statistics slow feature analysis(GSSFA). Highlights: A transition identification and monitoring scheme is proposed based on SFA. The trajectory-based transion monitoring method is presented with two statistics. Operating faults for transition switching are generated based on HAZOP. Two performance indexes (DT and RT) are introduced for the catastrophic failures.